“Fútbol callejero”: emerging educational processes of the social practice of mediation - Varotto, Nathan Raphael (2017)
The aim of this article was to understand the educational processes that emerged from the mediation by the social practice of the “Fútbol Callejero” in an extension project that occurred in Sao Carlos- -SP. The analysis considered 10 meetings which occurred from August/2015 to February/2016, registered in field diaries. To build up the results, which used a methodological based on phenomenology, emerged two different categories: a) To respect dialog; b) To play with other. From these results, we perceived that the experience from the fruition of the “Fútbol Callejero” collaborated to improve comprehension and to promote more cooperative, more respectful and supportive relationships.